MeWRKY IIas, subfamily genes of WRKY transcription factors from cassava, play an important role in disease resistance - Zhu, Shousong; Fan, Rouchen; Xiong, Xi; Jianjun Li; Xiang, Li; Hong, Yuhui; Ye, Yiwei; Zhang, Xiaofei; Yu, Xiaohui; Chen, Yinhua (Frontiers Media, 2022)
Cassava (Manihot esculenta Crantz) is an important tropical crop for food, fodder, and energy. Cassava bacterial blight (CBB) caused by Xanthomonas axonopodis pv. manihotis (Xam) occurs in all cassava growing regions and threatens global cassava production. WRKY transcription factor family plays the essential roles during plant growth, development, and abiotic or biotic stress. Particularly, previous studies have revealed the important role of the group IIa WRKY genes in plant disease resistance. However, a comprehensive analysis of group IIa subfamily in cassava is still missing. Here, we identified 102 WRKY members, which were classified into three groups, I, II, and III. Transient expression showed that six MeWRKY IIas were localized in the nucleus. MeWRKY IIas transcripts accumulated significantly in response to SA, JA, and Xam. Overexpression of MeWRKY27 and MeWRKY33 in Arabidopsis enhanced its resistance to Pst DC3000. In contrast, silencing of MeWRKY27 and MeWRKY33 in cassava enhanced its susceptibility to Xam. Co-expression network analysis showed that different downstream genes are regulated by different MeWRKY IIa members. The functional analysis of downstream genes will provide clues for clarifying molecular mechanism of cassava disease resistance. Collectively, our results suggest that MeWRKY IIas are regulated by SA, JA signaling, and coordinate response to Xam infection.